A new species, new immature stages, and new synonymy in Australian Dasybasis flies (Diptera: Tabanidae: Diachlorini) - Ferguson, David J.; Yeates, David K. (Zootaxa, 2015)
Australian beach sand is a productive habitat for lower brachyceran fly larvae but often overlooked by collectors. We collected two species of tabanid larvae from coastal beach sand in southern New South Wales in August 2013. Both species belong to the Dasybasis macrophthalma species-group of Mackerras (1959), one a new species, and the other D. exulans (Erichson, 1842). We describe both new immature stages and the new species adult as Dasybasis rieki sp. nov. (Diptera: Tabanidae: Diachlorini). Trojan (1994b) elevated the D. macrophthalma species group to the genus Sznablius. We review the evidence for the generic status of Sznablius, and synonymize it with Dasybasis.